Algerian high school students’ perceptions of the challenges of learning english as a second foreign language - Lebci, Zahra; Al-Hidabi, Dawood Abdulmalek Yahya (Asian Academic Research Associates, 2017)
This paper reports the outcome of a study carried out in four Algerian high schools with 240 Students to obtain a deeper insight into their perceptions of challenges that they are facing in Learning English as a Second Foreign Language in the classroom, in addition, to see whether the gender plays a vital role in challenges. Quantitative data were collected by means of students’ questionnaire. The results have shown that the majority of the respondents agree that all, except for one of the statements, which was "I think of a sentence in French first and then translate it into English" contribute to the challenges as English Language learners in Algeria. Hence, it can be concluded that there are six main challenges faced by Algerian students in learning English as a Second Foreign Language. These challenges are the lack of vocabulary in writing, the insufficient amount of speaking lessons to improve speaking skills, the time taken to recall exact pronunciation while giving the explanation, grammar problems in writing, oral fluency while presenting and the lack of confidence in reading in class.